Elucidating the interactive impact of tillage, residue retention and system intensification on pearl millet yield stability and biofortification under rainfed agro-ecosystems - Yogi, Akshay K.; Bana, Ram Swaroop; Godara, Samarth; Sangwan, Seema; Choudhary, Anil K.; Nirmal, Ravi C.; Bamboriya, Shanti D.; Shivay, Yashbir S.; Singh, Deepak; Singh, Teekam; Yadav, Achchhelal; Nagar, Shivani; et al. (Frontiers in Nutrition, 2023)
Micronutrient malnutrition and sub-optimal yields are the two major challenges under the fragile rainfed systems across the globe. To tackle these issues, climate-smart management strategies, such as conservation agriculture (CA) and system intensification of widespread millet systems, are pivotal in rainfed agro-ecologies. In this experiment, we studied the impact of diverse system-intensification options, residue management, and contrasting tillage practices on pearl millet yield stability, biofortification, and fatty acid profile of the pearl millet. Zero-tillage (ZT) systems with legume intercropping (cluster bean, cowpea, and chickpea), in additive series, significantly enhanced the productivity (7-12.5%), micronutrient biofortification [Fe (12.5%), Zn (4.9-12.2%), Mn (3.1-6.7%), and Cu (8.3-16.7%)], protein content (2.2-9.9%), oil content (1.3%) and fatty acid profile of pearl millet grains, compared to conventional tillage (CT) based sole cropping systems. The nexus of tillage, residue-recycling, and system-intensification analyzed using GGE analysis, highlighted that residue-retention in both (wet and dry) seasons coupled with ZT pearl millet + cowpea mustard (both with and without barley intercropping) system was the best combination for achieving stable yields and micronutrient fortification. Conclusively, ZT coupled with residue-recycling and legume intercropping can be recommended to attain stable yield levels and enhance the biofortification of pearl millet under rainfed agroecosystems of South Asia. Through field experiments and statistical analysis, the research demonstrates the effects of these factors on pearl millet and provides valuable insights for biofortification and food security. The manuscript presents the findings of the field experiments, detailing the effects of contrasting tillage, residue management, and intensification options on pearl millet biofortification and yield stability.The results suggest that ZT and crop residue retention can improve pearl millet production and nutrient content, enhancing food and nutrition security in arid and semi-arid regions. The manuscript also discusses the potential trade-offs and synergies between different agricultural practices and provides recommendations for further research and practical applications. By adopting sustainable agricultural practices such as ZT and crop residue retention, along with appropriate intensification options, pearl millet biofortification, yield stability, and other nutrition factors like grain protein and fatty acid content can be improved, ultimately contributing to enhanced food and nutrition security in vulnerable regions.